Creativity in the teaching of literature: Some strategic proposals - Cavallini Solano, Leda (2013)
This paper explains a pedagogical proposal forteaching Literature in the public institutions of thesecondary education. The premise is that reading literature must be an enjoyable experience in order to do ameaningful and successful teaching and learning process in the context of middle schools of the public educational system. In this proposal, imagination andcreativity are essential, whereas the literature, ratherthan an academic subject is, first of all, an expression ofthe arts that enriches our cultural heritage.